Pengaruh Marketing Mix 4p Terhadap Keputusan Konsumen Pada Produk Retail Teh Butong & Teh Tobasari PT. Perkebunan Nusantara IV Medan - Dinda Rizqa Aulia; Nurhayati Nurhayati (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
This research was conducted with the aim of investigating the influence of the 4P Marketing Mix on consumer decisions regarding PTPN IV Butong Tea & Tobasari Tea retail products. Marketing Mix 4P includes four main components, namely product, price, place and promotion, which are interrelated and have the potential to influence consumer decisions. In this context, Butong Tea & Tobasari Tea were chosen as retail products offered by PTPN IV. The research method used in this study involves interviews with willing sources as a means of collecting data. Research respondents were consumers of Butong Tea & Tobasari Tea who were randomly selected. The data collected will be analyzed using the narrative analysis method to identify the influence of each 4P Marketing Mix component on consumer decisions. The hope is that this research can provide more in-depth knowledge about the factors that influence consumer decisions in choosing Butong Tea & Tobasari Tea. Moreover, the main aim of this research is also expected to provide broader understanding for PTPN IV in optimizing their marketing strategy to increase product interest so that it influences consumer decisions. The conclusions from this research can contribute to knowledge and understanding of the influence of the 4P Marketing Mix on consumer decisions in the context of Butong Tea & Tobasari Tea retail products. Companies need to consider the principles of justice, business ethics, managerial skills, social responsibility, and halal transactions in marketing strategies and consumer decisions. This research can also provide practical input for PTPN IV and the tea industry in general in developing effective marketing strategies to increase sales and consumer satisfaction.